On the effectiveness of learning through the use of the web-based Laboratories– the experience of using the solar e-lab - Eleftheriou, Polyvios; Michaelides, Ioannis (My University, 2010)
This paper elaborates on the experience from the operation of the solar energy e-learning laboratory (Solar e-lab) in Cyprus, and analyses the results of the online evaluation submitted by the e-lab users. The aim of solar energy e-learning laboratory is to use web-based technology as a tool to make the laboratory facilities accessible to engineering students and technicians, including handicapped, located outside the e-lab premises anywhere in the world. In this way, the laboratory, its equipment and experimental facilities are available and can be shared by many people, thus reducing costs and widening educational experiences. Throughout its 5 years of operation, the solar e-lab has been accessed by users from over 400 locations from 75 countries spread all over the world. The total number of hits recorded on the site exceeded 1.2 million. Furthermore, a number of colleges and Universities are using the solar e-lab as part of their training programme. Judging from the online student evaluation reports sent to the solar e-lab administrator, it can be said that there is nearly excellent satisfaction by the users. The feedback provides useful information as to the students’ satisfaction with the e-lab interaction, its course content, and organisation.